ALG-2 Attenuates COPII Budding In Vitro and Stabilizes the Sec23/Sec31A Complex - la Cour, Jonas M. (Public Library of Science, 2013)
Coated vesicles mediate the traffic of secretory and membrane cargo proteins from the endoplasmic reticulum (ER) to the Golgi apparatus. The coat protein complex (COPII) involved in vesicle budding is constituted by a GTPase, Sar1, the inner coat components of Sec23/Sec24 and the components of the outer coat Sec13/Sec31A. The Ca(2+)-binding protein ALG-2 was recently identified as a Sec31A binding partner and a possible link to Ca(2+) regulation of COPII vesicle budding. Here we show that ALG-2/Ca(2+) is capable of attenuating vesicle budding in vitro through interaction with an ALG-2 binding domain in the proline rich region of Sec31A. Binding of ALG-2 to Sec31A and inhibition of COPII vesicle budding is furthermore dependent on an intact Ca(2+)-binding site at EF-hand 1 of ALG-2. ALG-2 increased recruitment of COPII proteins Sec23/24 and Sec13/31A to artificial liposomes and was capable of mediating binding of Sec13/31A to Sec23. These results introduce a regulatory role for ALG-2/Ca(2+) in COPII tethering and vesicle budding.